Treacle controls the nucleolar response to rDNA breaks via TOPBP1 recruitment and ATR activation - Mooser, C; Symeonidou, I; Leimbacher, P; Ribeiro, A; Shorrocks, A; Jungmichel, S; Larsen, S; Knechtle, K; Jasrotia, A; Zurbriggen, D; Jeanrenaud, A; Leikauf, C; et al. (Nature Research, 2020)
Induction of DNA double-strand breaks (DSBs) in ribosomal DNA (rDNA) repeats is associated with ATM-dependent repression of ribosomal RNA synthesis and large-scale reorganization of nucleolar architecture, but the signaling events that regulate these responses are largely elusive. Here we show that the nucleolar response to rDNA breaks is dependent on both ATM and ATR activity. We further demonstrate that ATM- and NBS1-dependent recruitment of TOPBP1 in the nucleoli is required for inhibition of ribosomal RNA synthesis and nucleolar segregation in response to rDNA breaks. Mechanistically, TOPBP1 recruitment is mediated by phosphorylation-dependent interactions between three of its BRCT domains and conserved phosphorylated Ser/Thr residues at the C-terminus of the nucleolar phosphoprotein Treacle. Our data thus reveal an important cooperation between TOPBP1 and Treacle in the signaling cascade that triggers transcriptional inhibition and nucleolar segregation in response to rDNA breaks.